You are on page 1of 12

Partial Fractions

Addition & Subtraction


of Algebraic Fractions
Given two or more

fractions, we may add or


subtract them to form one single fraction.
For example:
1
1

x 1 x 1
( x 1) ( x 1)

( x 1)( x 1)
How
about
2
2
the reverse
x 1
process?

Partial Fractions
In the

reverse process, we try to express a


fraction as a sum of more than one fractions.
5
For example: Given
x2 x 6
1
1
we can try to express it as

x2 x3
These are called

partial fractions of the original fraction.

Before we proceed
If the degree of the
numerator of the given
fraction is equal to or greater
than that of the denominator,
divide the numerator by the
denominator until a
remainder is obtained, which
is of lower degree than the
denominator.
For example:

x -1

x3
x2 x 2

x2 x 2 x3

x3 + x2 2x
- x2 + 2x
-x2 x + 2
3x - 2
x3
x2 x 2
( x 2 x 2)( x 1) (3 x 2)

x2 x 2
3x 2
( x 1) 2
x x2

Type I:
Denominator with only linear factors

To every linear factor, (ax + b), the corresponding partial

fraction is in the form


For example:

A
(ax b)

where A is a constant.

11x 12
(2 x 3)( x 2)( x 3)
A
B
C

2x 3 x 2 x 3

Now, the
problem is to
find the
constants A, B
and C.

11x 12
A
B
C

(2 x 3)( x 2)( x 3) 2 x 3 x 2 x 3

11x 12
A( x 2)( x 3) B(2 x 3)( x 3) C (2 x 3)( x 2)

(2 x 3)( x 2)( x 3)
(2 x 3)( x 2)( x 3)
11x + 12 A(x + 2)(x 3) + B(2x + 3)(x 3) + C(2x + 3)(x + 2)
Put x = 3,
Put x = - 2,

11(3) + 12 = C(6 + 3)(3 + 2)


Or,
C=1
11(-2) + 12 = B[2(-2) + 3](-2 -3)
Or,
B = -2

Put x = -3/2, 11(-3/2) + 12 = A(- 3/2 + 2)(- 3/2 3)


Or,
A=2
11x 12
2
2
1

( 2 x 3)( x 2)( x 3) 2 x 3 x 2 x 3

Type II:
Denominator with a quadratic factor

To every quadratic factor, ax2 + bx + c, there corresponds


a partial fraction in the form
Ax B

ax bx c
2

Note that fractions which can be split into partial fractions are necessarily
proper, and thus, the resulting partial fractions themselves are always proper
Example:

3x 1
A
Bx C

2
2
( x 1)( x 1) ( x 1) ( x 1)

3x 1
A
Bx C

2
2
( x 1)( x 1) ( x 1) ( x 1)

3x 1
A( x 2 1) ( Bx C )( x 1)

2
( x 1)( x 1)
( x 1)( x 2 1)

(3x + 1) A(x2 + 1) + (Bx + C)(x 1)


Put x = 1,

3 + 1 = A(1 + 1)
Or, A = 2

Put x = 0,

1 = A + C(-1)
Or, C = 1

Equating the coefficient of x2:


Or, B = -2

0=A+B

3x 1
2
1 2x

2
2
( x 1)( x 1) x 1 x 1

Type III:
Denominator with a repeated factor

To every repeated factor like (ax + b)2 in the


denominator, there corresponds partial fractions in the
form A
B
ax b

and

(ax b) 2

Similarly, for factor like (ax + b)3 in the denominator,


there corresponds partial fractions in the form
A
B
C
,
and
2
ax b (ax b)
(ax b) 3
Example:
1
A
B
C

( x 2)( x 1)

x2

x 1 ( x 1) 2

1
( x 2)( x 1) 2
1

( x 2)( x 2 2 x 1)

A
Bx K

2
x 2 x 2x 1

x2
A

x2
A

x2

B ( x 1) B K
( x 1) 2
B ( x 1) B K

2
( x 1)
( x 1) 2
B
C

x 1 ( x 1) 2

Type II

1
A
B
C

2
( x 2)( x 1)
x 2 x 1 ( x 1) 2

1
A( x 1) 2 B ( x 1)( x 2) C ( x 2)

2
( x 2)( x 1)
( x 2)( x 1) 2

1 A(x 1)2 + B(x 1)(x+ 2) + C(x + 2)


Put x = - 2, 1 = A(- 2 1)2
Or, A = 1/9
Put x = 1,

1 = C(1 + 2)
Or, C = 1/3

Equating the coefficients of x2: 0 = A + B


Or, B = -1/9

1
1
1
1
Thus,

2
( x 2)( x 1)
9( x 2) 9( x 1) 3( x 1) 2

How about this?


Express

as partial fractions:

2x 1
5
x ( x 1)